Model Penyelesaian Sengketa dan Peradilan Adat di Aceh - Nanda Amalia; Mukhlis Mukhlis; Yusrizal Yusrizal (Jurnal Hukum IUS QUIA IUSTUM, 2018)
This research had two objectives: first to explore the opinions of Aceh community, especially those who lived in Gampong (village) area, about the implementation of customary court in Gampong and second to illustrate the dispute resolution models used by the Gampong Customary Court and any considerations underlying its judgment in making decisions. This was a qualitative research, using a socio-legal approach that specifically took place in Lhokseumawe, Northern Aceh, Meulaboh and Tapak Tuan. In addition to literature studies, the data collection was also done through field research. This study concluded that, first, the existence of Gampong customary court is perceived by the society to have an alternative and positive potential as the resolution of minor violations that could be resolved by the community. In addition, the existence of this customary court could reduce the accumulated cases in court as well as could help the community access the protection of their rights. Second, there are two models of dispute resolution in Gampong, namely a simple dispute resolution model with the involvement of Geuchik and the element of Tuha Peut Gampong. Another model is a dispute resolution model that resembles formal trials based on the customary court guidelines issued by Aceh Customary Board.